Quality Characteristics of Fermented Semi-Dry Chicken Sausages during Storage at Refrigeration (4+10C) Temperature - Rao, Eswara; P.R.S., B. Moorthy; K., Sudhakara Redy (Journal of Meat Science, 2012)
In this investigation, proximate composition, physico-chemical, microbiological and oganoleptic characteristics of semi-dry fermented chicken sausages using different lactic acid bacteria viz., Lactobacillus casei, Lactobacillus plantarum and Pediococcus pentosaceus were evaluated at regular intervals during storage at refrigeration (4+10C) temperature. The per cent moisture of semi-dry fermented mutton sausages as effected by lactic acid bacteria were significantly (P>0.01) lower where as protein and fat were higher than control. Among treatments lower per cent moisture and higher protein and fat were observed in sausages fermented with LP followed by PP and LC. Significantly (P>0.01) lower pH, water activity, TBARS values and cooking yield were observed in sausages fermented with LC, LP and PP than control. Significantly (P>0.01) higher shrinkage values were observed in semi- dry fermented sausages than control at refrigeration temperatures. Among treatments significantly (P>0.01) lower pH, water activity, TBARS values and cooking yield were observed in chicken sausages fermented with LP than PP and LC at refrigeration temperatures. Shrinkage values were significantly (P>0.01) higher in sausages fermented with LP followed by PP and LC. Significant (P>0.01) decrease in water activity, TBARS values and cooking yield and increase(P>0.01) in shrinkage during storage at refrigeration temperature. There was higher (P>0.01) total plate count, yeast and mould count, coliform count and salmonella count were noticed in control than sausages treated with LC, LP and PP at refrigeration storage. Among the treatments significantly (P>0.01) higher total plate count, yeast and mould count and lower (P>0.01) Salmonella and Coliform count were observed in sausages fermented with LP followed by PP and LC. There was a significant (P>0.01) increase in total plate count and yeast and mould count whereas Coliform and Salmonella counts were decreased during storage at refrigeration temperatures in semi-dry fermented chicken sausages. The psychrophilic count was not detected in semi-dry fermented chicken sausages treated with LC, LP and PP during 10 days of storage. Among treatments significantly (P>0.01) lower psychrophilic counts were noticed in sausages fermented with LP followed by PP and LC. With regards to the organoleptic characteristics significantly (P>0.01) higher colour, flavour and overall acceptability and lower juiciness and tenderness were noticed in sausages fermented with LC, LP and PP than control at refrigeration storage. Among treatments significantly higher colour and overall acceptability scores and lower juiciness and tenderness scores were noticed in sausages fermented with LP followed by PP and LC. But no significant difference in flavour was noticed in sausages fermented with LC, LP and PP at refrigeration temperature. There was a significant (P>0.01) decrease in colour, flavour, juiciness, tenderness and overall acceptability scores
Keywords: Chicken; semi-dry fermented sausages; lactic acid bacteria